The Influence of Classroom Environment on Undergraduate Student Learning Outcomes - 1.Dr. M. Qadeer, 2. Emaan Mustafa, 3. Saira Arshad, 4. Malaika (International Research Journal of Arabic and Islamic Studies, 2024)
The classroom experience is significant to the learning outcomes of undergraduate students because it affects academic performance and engagement. A positive learning environment increases motivation alongside cognitive and participation levels among undergraduates. An approach to learning that considers class design, physical conditions of the room, and pedagogical materials available affects student’s attention span, information retention, and accomplishment of academic objectives. Evidence verifies that lack of order in classroom management stifles progress, while well-ordered presentation design provides stimulating learning environments that achieve profound learning. These include basic and essential features of the room such as windows, doors, furnishings, heat and lighting. It also encompasses social dimensions, such as interactions between students and teachers, interactions among students, expectations and rules of the class, and management style which are equally important to motivate undergraduates to participate and actively engage. The possibility of controlling and modifying class layouts contributes as well to ownership over space which helps in fostering belonging and control needed for intellectual growth at the undergraduate level.